Study of bookbindings of Jacques-Nicolas Colbert deposited at the Complutense Library - de Francisco Olmos, José María; Carpallo Bautista, Antonio (Revista General de Información y Documentación, 2017)
This investigation studies the bindings of the family Colbert deposited in the Historical Library Marquess of Valdecilla of the Complutensian University of Madrid. This first study tries to identify the superlibris of Jacques-Nicolas Colbert, Archbishop of Rouen, which appear on a covers of books, helped by the different types of anagrams and decorative structures of the box; also there are studied the materials and the technologies of construction of the bindings, the decoration of the loin (bands and panel area between the bands), top of head edge, square, head-cap and endpaper, many of them decorated with marbled papers, as well as his condition of conservation.